Relationship between sufficiency and usefulness of patient education: A cross‐sectional study of patients with chronic kidney disease - Inkeroinen Saija; Virtanen Heli; Kilpi Taina; Laulaja Johanna; Puukka Pauli; Tuominen Riitta; Leino-Kilpi Helena (Wiley, 2022)
The aim of this descriptive study was to analyze the relationship between the sufficiency and usefulness of patient education from the perspective of people with chronic kidney disease. The goal was to discover whether both sufficiency and usefulness need to be analyzed in the quality evaluation of patient education. Patients undergoing predialysis or home dialysis care in Finland (N = 162) evaluated both the sufficiency and usefulness of patient education provided by nephrology nurses by using parallel structured questionnaires. A strong relationship was found between the sufficiency and usefulness of patient education. The relationship was significant across all dimensions of empowering knowledge, but no systematic association was found between the sufficiency-usefulness relationship and background variables. Depending on the purpose of evaluating patient education, either aspect, that is, sufficiency or usefulness, can be used, but it is not necessary to use both due to their strong inter-correlation. In terms of implications for practice, consideration of both sufficiency and usefulness is important when providing empowering patient education for people undergoing pre- or home dialysis, but only one aspect needs to be evaluated.